2017
DOI: 10.1002/2211-5463.12179
|View full text |Cite
|
Sign up to set email alerts
|

Serine phosphorylation of the cotton cytosolic pyruvate kinase GhPK6 decreases its stability and activity

Abstract: Pyruvate kinase (PK, http://www.chem.qmul.ac.uk/iubmb/enzyme/EC2/7/1/40.html) is an important glycolytic enzyme involved in multiple physiological and developmental processes. In this study, we demonstrated that cotton cytosolic pyruvate kinase 6 (GhPK6) was phosphorylated at serines 215 and 402. Phosphorylation of GhPK6 at serine 215 inhibited its enzyme activity, whereas phosphorylation at both serine sites could promote its degradation. The phosphorylation‐mediated ubiquitination of GhPK6 was gradually atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Ubiquitin-dependent degradation of glycolytic enzymes has been previously shown to exert strong modulatory effects on plantand animal physiology. Zhang et al reported that phosphorylation-activated ubiquitination of cytosolic pyruvate kinase 6 in cotton might be associated with accelerated fiber elongation 40 . In another study, Almeida and colleagues showed that APC/C-induced degradation of 6-phosphofructokinase significantly suppressed glycolysis, and thus proliferation, in tumor cells 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitin-dependent degradation of glycolytic enzymes has been previously shown to exert strong modulatory effects on plantand animal physiology. Zhang et al reported that phosphorylation-activated ubiquitination of cytosolic pyruvate kinase 6 in cotton might be associated with accelerated fiber elongation 40 . In another study, Almeida and colleagues showed that APC/C-induced degradation of 6-phosphofructokinase significantly suppressed glycolysis, and thus proliferation, in tumor cells 41 .…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we initially showed that copper induces the increase in HK activity through MAPKs activation whereas it inhibits PK through CDPKs and MAPKs activation indicating that phosphorylation of HK and PK enzymes regulate these activities. In this sense, it has been shown that PK activity is inhibited by phosphorylation of ser215 in soybean and cotton cells and the additional phosphorylation in ser402 enhances its degradation in the proteasome ( Tang et al., 2003 ; Zhang and Liu, 2017 ). In addition, it has been shown that HK1 and HK2 are activated by c-Src tyrosine kinase that phosphorylates tyr73, which favors proliferation, migration and invasion of human tumoral cells ( Zhang et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation increases the stability of PK under acidic condition (Schwägele et al ., ). Phosphorylation of pyruvate kinase at serine 215 inhibits its enzyme activity, so it can be hypothesised that the stability of PK was increasing and the activities was inhibited after phosphorylation (Zhang & Liu, ). The phosphorylation level of PK was higher in the S group, which corresponded to the determined glycolytic rate.…”
Section: Discussionmentioning
confidence: 99%